Revival from Below - Ali Altaf Mian (International Institute of Islamic Thought, 2020)
Brannon D. Ingram’s monograph casts fresh light on the global life of the Deoband movement, which is “arguably the most influential Muslim reform and revival movement outside of the Middle East in the last two centuries” (2). The seminary (madrasa) associated with this movement was founded in 1866 in the North Indian town of Deoband by religious scholars (ʿulamāʾ) who were at once Ḥanafī jurists and Chishtī ṣūfīs. They reimagined “Sufism through law, Sufism as ethics, Sufism in politics” (3). The author elucidates this movement’s internal differences and uses its complex history, in both South Asia and South Africa, to illuminate broader features of global Islam, including “the place of Sufism in the modern world, the position of the ʿulama in Muslim public life, and the very notion of Islamic tradition” (11). The study is grounded in a range of primary texts authored by and about Deobandī scholars. The book’s title, Revival from Below, refers to how the Deobandīs have pursued “a bottom-up reform largely invisible relative to the top-down reform of Islamist political projects” (18). I will return to the limitation of this argument at the end of this review. Here, let us appreciate how the author approaches the binaries that structure his object of study in a dialectical fashion: “Deobandi tradition arises out of a tension—sometimes productive, sometimes strained—between the anthropocentric and the bibliocentric, between the centrifugal force of a global movement and the centripetal force of intimate encounters, between the dispersal of books and the proximity of bodies, between esoteric centers and exoteric peripheries, and above all, between the ‘little’ tradition of the maslak, to which they adhere as Deobandis, and the ‘great’ tradition of the Sunna, to which they adhere as Muslims” (23-24).